Self-Discipline for Futsal Players - Mahmood Mohammed Al- Assaf , Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims at building a self-discipline scale for futsal players in scientific and humanitarian colleges at the University of Mosul. To achieve the aim of the research, the researcher used the descriptive method with a survey due to its appropriateness. The society was made up of players of futsal teams in scientific and humanitarian colleges playing at the university championship for the academic year 2017-2018, reaching 239 from 21 colleges divided into 13 scientific and 8 humanitarian. After excluding 13 players, the sample was 226. Due to the absence of a scale of self-discipline for futsal players, the researcher made his own scale. Surface validity of the scale items was found using the expert’s opinions. The items that had 75% agreement were kept, omitting the items with a lower ratio of agreement. Content validity and discrimination validity were found using extreme groups and internal coordination strategies. (31) Items were omitted; the scale in its final form, after item statistical analysis, consisted of (31) items divided into three axes (behavioral knowledge, emotional). Stability was found using the Kronbach formula on a computer reading (0.77), a reliable degree.